The influence of lower limb amputation level on the approach in the amputee long jump - Nolan, L.; Lees, A. (Journal of Sports Sciences, 2007)
In this study, we investigated the adjustments to posture, kinematic and temporal characteristics of performance made by lower limb amputees during the last few strides in preparation for long jump take-off. Six male unilateral trans-femoral and seven male unilateral trans-tibial amputees competing in a World Championships final were filmed in the sagittal plane using a 100-Hz digital video camera positioned so that the last three strides to take-off were visible. After digitizing using a nine-segment model, a range of kinematic variables were computed to define technique characteristics. Both the trans-femoral and trans-tibial athletes appeared to achieve their reduction in centre of mass during the flight phase between strides, and did so mainly by extending the flight time by increasing stride length, achieved by a greater flexion of the hip joint of the touch-down leg. The trans-tibial athletes appeared to adopt a technique similar to that previously reported for able-bodied athletes. They lowered their centre of mass most on their second last stride (-1.6% of body height compared with -1.4% on the last stride) and used a flexed knee at take-off on the last stride, but they were less able to control their downward velocity at touch-down (-0.4 m · s-1). Both this and their restricted approach speed (8.9 m · s-1 at touch-down), rather than technique limitations, influenced their jump performance. The trans-femoral athletes lowered their centre of mass most on the last stride (-2.3% of body height compared with -1.6% on the second last stride) and, as they were unable to flex their prosthetic knee sufficiently, achieved this by abducting their prosthetic leg during the support phase, which led to a large downward velocity at touch-down (-0.6 m · s-1). This, combined with their slower approach velocity (7.1 m · s-1 at touch-down), restricted their performance.